Naskah Drama Pengembala dan Biri-Biri: Analisis Unsur Intrinsik dalam Pembelajaran - Mala, Elvita (Attractive : Innovative Education Journal, 2024)
This study aims to analyze the intrinsic elements in the script of "The Shepherd and the Sheep," adapted from the famous Upin-Ipin story, using the library research method. The research explores the themes, characters and characterization, plot, setting, moral message, dialogue, and language style present in the script. The literature review found that the script's central theme is social, emphasizing the importance of honesty. The central characters in the script include Jarjit as the shepherd, Upin and Ipin as farmers, and Mail as the wolf, each playing a significant role in the progressive plot. The setting at the hillside, daytime setting, and simple social setting reinforce the narrative and characterization. Communicative dialogue and comparative and emphatic language styles add depth to the script and facilitate understanding for readers or viewers. The novelty of this research lies in utilizing a relevant and engaging story for students, thereby enhancing the effectiveness of literature learning and instilling ethical and social values. This study contributes significantly to literature teaching in schools through an interactive and meaningful approach via in-depth library research Keywords: Intrinsic Element, Drama Script, Educations